Original paperImpact of intraoperative MRI/TRUS fusion on dosimetric parameters in cT3a prostate cancer patients treated with high-dose-rate real-time brachytherapy - Gomez-Iturriaga, Alfonso; Crook, Juanita; Casquero, Francisco; Carvajal, Claudia; Urresola, Arantxa; Canteli, Begońa; Ezquerro, Ana; Hortelano, Eduardo; Cacicedo, Jon; Espinosa, Jose Maria; Perez, Fernando; Minguez, Pablo; et al. (Journal of Contemporary Brachytherapy, 2014)
Purpose: The purpose of this study was to evaluate the impact of intraoperative MRI/TRUS fusion procedure in cT3a prostate cancer patients treated with high-dose-rate (HDR) real-time brachytherapy. Material and methods : Prostate gland, dominant intraprostatic lesions (DILs), and extracapsular extension (ECE) were delineated in the pre-brachytherapy magnetic resonance images (MRI) of 9 consecutive patients. The pre-implant P-CTV US (prostate clinical target volume) was defined as the prostate seen in the transrectal ultrasound (TRUS) images. The CTV MR includedthe prostate with the ECE image (ECE-CTV) as defined on the MRI. Two virtual treatment plans were performed based on the MRI/TRUS fusion images, the first one prescribing 100% of the dose to the P-PTV US , and the second prescribing to the PTV MR . The implant parameters and dose-volume histogram (DVH) related parameters of the prostate, OARs, and ECE were compared between both plans. Results : Mean radial distance of ECE was 3.6 mm (SD: 1.1). No significant differences were found between prostate V 100 , V 150 , V 200 , and OARs DVH-related parameters between the plans. Mean values of ECE V 100 , V 150 , and V 200 were 85.9 % (SD: 15.1), 18.2 % (SD: 17.3), and 5.85 % (SD: 7) when the doses were prescribed to the PTV US , whereas ECE V 100 , V 150 , and V 200 were 99.3 % (SD: 1.2), 45.8 % (SD: 22.4), and 19.6 % (SD: 12.6) when doses were prescribed to PTV MR (p = 0.028, p = 0.002 and p = 0.004, respectively). Conclusions : TRUS/MRI fusion provides important information for prostate brachytherapy, allowing for better coverage and higher doses to extracapsular disease in patients with clinical stage T3a.